Therapeutic effect of molecular hydrogen in corneal UVB-induced oxidative stress and corneal photodamage. Issue 1 (December 2017) - Cejka, Cestmir; Kossl, Jan; Hermankova, Barbora; Holan, Vladimir; Kubinova, Sarka; Zhang, John; Cejkova, Jitka
Abstract The aim of this study is to examine whether molecular hydrogen (H2 ) is able to reduce oxidative stress after corneal damage induced by UVB irradiation. We previously found that UVB irradiation of the cornea caused the imbalance between the antioxidant and prooxidant enzymes in the corneal epithelium, followed by the imbalance between metalloproteinases and their physiological inhibitors (imbalances in favour of prooxidants and metalloproteinases) contributing to oxidative stress and development of the intracorneal inflammation. Here we investigate the effect of H2 dissolved in PBS in the concentration 0.5 ppm wt/vol, applied on rabbit corneas during UVB irradiation and healing (UVB doses 1.01 J/cm2 once daily for four days). Some irradiated corneas remained untreated or buffer treated. In these corneas the oxidative stress appeared, followed by the excessive inflammation. Malondiladehyde and peroxynitrite expressions were present. The corneas healed with scar formation and neovascularization. In contrast, in H2 treated irradiated corneas oxidative stress was suppressed and malondiladehyde and peroxynitrite expressions were absent. The corneas healed with the restoration of transparency. The study provides the first evidence of the role of H2 in prevention of oxidative and nitrosative stress in UVB irradiated corneas, which may represent a novel prophylactic approach to corneal photodamage.